2020
DOI: 10.1039/c9sc05671h
|View full text |Cite
|
Sign up to set email alerts
|

Disruption of microtubule function in cultured human cells by a cytotoxic ruthenium(ii) polypyridyl complex

Abstract: Treatment of cultured human cell lines with a cytotoxic IC50 dose of ∼2 μM tris(diphenylphenanthroline)ruthenium(ii) chloride (RPC2) retards or arrests microtubule motion as tracked by visualizing fluorescently-tagged microtubule plus end-tracking proteins.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

3
36
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 23 publications
(39 citation statements)
references
References 68 publications
(83 reference statements)
3
36
0
Order By: Relevance
“…Immunofluorescence studies with GM130 (cis-Golgy protein), TGN46 (trans-Golgy protein), KDEL (endoplasmic reticulum protein retention receptor) and LAMP (lysosome-associated membrane glycoprotein)antibodies demonstrated that compound 6 did not colocalize with any of them (Figure 4a).Correlation analysis including Pearson's R value as well as Manders' M1 and Manders's M2values confirmed the lack of colocalisation of the tested probes with complex 6(Figure 4b). It is possible that the cytosolic localisation of our complex could be explained by its binding to the cytoskeleton as recently reported for structurally similar complex by the group of MacDonnell 67. …”
supporting
confidence: 66%
“…Immunofluorescence studies with GM130 (cis-Golgy protein), TGN46 (trans-Golgy protein), KDEL (endoplasmic reticulum protein retention receptor) and LAMP (lysosome-associated membrane glycoprotein)antibodies demonstrated that compound 6 did not colocalize with any of them (Figure 4a).Correlation analysis including Pearson's R value as well as Manders' M1 and Manders's M2values confirmed the lack of colocalisation of the tested probes with complex 6(Figure 4b). It is possible that the cytosolic localisation of our complex could be explained by its binding to the cytoskeleton as recently reported for structurally similar complex by the group of MacDonnell 67. …”
supporting
confidence: 66%
“…The in vitro tubulin polymerization assay is based on the fractionation of depolymerized (soluble) and polymerized α-tubulin fractions of drug-treated cells in hypotonic buffer conditions with their subsequent analysis by Western blotting. 33 The hypotonic buffer was reported to keep assembled microtubules in a polymerized state and depolymerized tubulin in a soluble form. Therefore, these lysis conditions allow for the preservation of the degree of tubulin polymerization in drug-treated cells.…”
Section: Resultsmentioning
confidence: 99%
“…The metal fragments were chosen based on the previous literature reports about related paullones with improved biological characteristics, 30 32 additionally to the ability of various Ru complexes to target tubulin polymerization. 33 , 34 We discuss the synthesis and structural features of novel compounds, their anticancer activity in cancer cell lines, as well as preliminary in vivo data. Importantly, we demonstrate that similar to the reported core latonduine structure 17 the mechanism of action of novel compounds was linked to microtubule-destabilizing properties.…”
Section: Introductionmentioning
confidence: 99%
“…[11] There are only a handful of studies, that considered their potential antimetastatic activity. It was shown that Ru polypyridyl complexes can influence the cellmatrix adhesion properties [14,15], disrupt microtubule function by acting as microtubule stabilizing agents [16] as well as decrease cell migration capability. [14,[17][18][19] Inspired by these findings, we have decided to thoroughly investigate the in vitro behavior of a group of Ru(II) polypyridyl complexes containing 2,2'-bipyridine ligand substituted by a semicarbazone2-formylopyridine moiety (L1, Fig.1 and Scheme 1), focusing on their impact on the alteration of tumor cells' adhesion properties that is relevant in anti-metastatic treatment.…”
Section: Introductionmentioning
confidence: 99%